NON-INVASIVE VENTILATION IN CARDIAC PULMONARY EDEMA – NARRATIVE REVIEW - Szubert, Izabela; Suchecka, Julia; Lamorski, Jakub; Stępień, Gabriela; Nesterak, Wiktor; Chylewski, Michał; Chudecka, Karolina; Kędzierska, Aleksandra; Przewoźna, Urszula; Józwa, Katarzyna (International Journal of Innovative Technologies in Social Science, 2026)
Non-invasive ventilation (NIV), including continuous positive airway pressure (CPAP) and bilevel positive airway pressure (BiPAP), is a cornerstone in the management of acute cardiogenic pulmonary edema (CPE). NIV improves oxygenation, reduces the work of breathing, and exerts favorable hemodynamic effects by decreasing preload and afterload. These physiological mechanisms contribute to rapid clinical stabilization in critically ill patients. Current estimates suggest that the condition affects approximately 1 million patients with pulmonary edema secondary to cardiac causes. (1) Patients with CPE present with a wide range of symptoms, most notably dyspnea, reflecting the acute nature of the condition, underscoring the severity and clinical importance of the issue. Overall, NIV represents an effective first-line supportive therapy in patients with acute CPE, although further research is needed to clarify its effect on long-term outcomes. Available data consistently demonstrate that NIV reduces the need for endotracheal intubation and improves short-term physiological parameters, particularly when initiated early. (2) However, its impact on mortality remains inconsistent across studies. This review synthesizes current evidence on NIV in cardiogenic pulmonary edema, focusing on underlying mechanisms, clinical effectiveness, and comparative data on CPAP and BiPAP, with emphasis on their role in emergency and intensive care settings.